2020
DOI: 10.26803/ijlter.19.9.7
|View full text |Cite
|
Sign up to set email alerts
|

Novice Teachers’ Challenges and Coping Strategies in Qatari Government Schools

Abstract: This study examined the challenges novice teachers encountered in Qatari government schools and the coping strategies they adopt. A qualitative study was conducted using semi-structured interviews with 15 novice teachers during their initial years of teaching. The findings demonstrated that most participants faced several personal challenges and other challenges within and beyond the school. Findings also indicated that these teachers confronted these challenges using various coping strategies. The challenges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Traditionally prepared students in China generally take three types of courses: general education courses, subject-specific courses, and teacher education courses, and they are required to devote more than half of their professional learning time to general education and teacher education (Qiao & Lai, 2019; Zhou, 2014), which makes it difficult for them to learn subject knowledge in depth and limiting their future development of curriculum leadership to some extent. Another outstanding problem is the failure to link theory and practice in teacher education programs, resulting in a considerable gap between the curriculum teachers learn in teacher education colleges and those in primary and secondary schools (Al-Naimi, et al, 2020). Thus, some teachers are unable to apply the theories learned in teacher preparation programs to classroom practice (Qadhi et al, 2020), which affects teachers’ performance in teaching practice.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally prepared students in China generally take three types of courses: general education courses, subject-specific courses, and teacher education courses, and they are required to devote more than half of their professional learning time to general education and teacher education (Qiao & Lai, 2019; Zhou, 2014), which makes it difficult for them to learn subject knowledge in depth and limiting their future development of curriculum leadership to some extent. Another outstanding problem is the failure to link theory and practice in teacher education programs, resulting in a considerable gap between the curriculum teachers learn in teacher education colleges and those in primary and secondary schools (Al-Naimi, et al, 2020). Thus, some teachers are unable to apply the theories learned in teacher preparation programs to classroom practice (Qadhi et al, 2020), which affects teachers’ performance in teaching practice.…”
Section: Discussionmentioning
confidence: 99%
“…[28] revealed that secondary teachers from different content areas in one school in the Midwest region in the United States of America adjusted their lessons to the New Normal, which they believed could have an effect on the delivery of lessons. [2] divulged in their study that novice teachers used coping mechanisms to obtain a state of psychological and spiritual calm in teaching in the New Normal. Relatedly, [23] found out that language teachers maintained positivity during the COVID-19 pandemic.…”
Section: Strategizing Ways To Promote Transfer Of Learningmentioning
confidence: 99%
“…Despite the efforts made by the Department of Basic Education and the Department of Higher Education and Training in South Africa to support junior teachers, challenges experienced by these teachers persist (Esau & Maarman, 2021). Studies conducted in countries such as Turkey, Pakistan, United States of America and Qatar revealed that junior teachers lack adequate professional support and may feel unprepared to handle academic issues and manage learner behaviour (Ahmed et al, 2020;AL-Naimi et al, 2020;Ross-Hain, 2020;Kozikoğlu and Senemoğlu, 2018). It is imperative to acknowledge that pervasive challenges are not only confined to junior teachers within the African continent as they are also widely experienced by other teachers across the globe (Lodge et al, 2018;Abdurrahman, 2016).…”
Section: Introductionmentioning
confidence: 99%